Development of Digestive System Magazine Material Based on the Inventory of Medicinal Plants - Agus Kurniasi; Ruqiah Ganda Putri Panjaitan; Eko Sri Wahyuni (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2026)
Learning materials serve as a medium for conveying information, to help students understand the material being taught. Generally, learning media contains material sourced from textbooks, but it can also be packaged based on research results relevant to the subject matter. In this study, the suitability of an educational magazine on the digestive system was evaluated. The learning material was derived from a medicinal plant inventory conducted in Tebing Batu Village, Sambas Regency, which identified various types of plants used by the local community to treat digestive disorders. The development was carried out by following the five stages of Sugiyono’s model: potential and issues, data collection, product design, validation, and revision. Five experts assessed the product’s validity in terms of presentation, content, and language using Lawshe’s method, which involves calculating the Content Validity Ratio and Content Validity Index. The assessment results showed that each aspect received a CVR score of 1.00, and the overall CVI score was 1.00, indicating a high level of validity. Meanwhile, reliability was tested using the ICC, yielding a value of 0.505, which falls within the “fair to good” category. Therefore, the magazine can be considered feasible and sufficiently reliable as an instructional resource. The development of this media, which is based on local resources, demonstrates the potential for utilizing research findings as a learning resource that can support instruction on the digestive system.